2017
DOI: 10.1136/oemed-2017-104319
|View full text |Cite
|
Sign up to set email alerts
|

Childhood adversity, adult socioeconomic status and risk of work disability: a prospective cohort study

Abstract: ObjectivesTo examine the combined effects of childhood adversities and low adult socioeconomic status (SES) on the risk of future work disability.MethodsIncluded were 34 384 employed Finnish Public Sector study participants who responded to questions about childhood adversities (none vs any adversity, eg, parental divorce or financial difficulties) in 2008, and whose adult SES in 2008 was available. We categorised exposure into four groups: neither (reference), childhood adversity only, low SES only or both. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 45 publications
(34 reference statements)
10
36
0
Order By: Relevance
“…Some predictors of mental health-related work disability have been identified (Halonen et al, 2017 them. The association between parents' mental disorders and offspring's early work disability due to mental disorders may be direct as indicated by the evidence on heritability of mental disorders (Franic, Middeldorp, Dolan, Ligthart, & Boomsma, 2010;Kendler, Ohlsson, Lichtenstein, Sundquist, & Sundquist, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some predictors of mental health-related work disability have been identified (Halonen et al, 2017 them. The association between parents' mental disorders and offspring's early work disability due to mental disorders may be direct as indicated by the evidence on heritability of mental disorders (Franic, Middeldorp, Dolan, Ligthart, & Boomsma, 2010;Kendler, Ohlsson, Lichtenstein, Sundquist, & Sundquist, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The association between parents' mental disorders and offspring's early work disability due to mental disorders may be direct as indicated by the evidence on heritability of mental disorders (Franic, Middeldorp, Dolan, Ligthart, & Boomsma, 2010;Kendler, Ohlsson, Lichtenstein, Sundquist, & Sundquist, 2018). Although there is evidence for early risk factors for work disability in general (Gravseth et al, 2007;Halonen et al, 2017;von Bondorff et al, 2015), surprisingly few studies have examined work disability in early adulthood and their possible risk factors from adolescence. Although there is evidence for early risk factors for work disability in general (Gravseth et al, 2007;Halonen et al, 2017;von Bondorff et al, 2015), surprisingly few studies have examined work disability in early adulthood and their possible risk factors from adolescence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers have suggested that SPA should directly reflect life expectancy differences, 38 where retirement eligibility age is determined by the type of job. 39 Alternatively, the eligibility age requirement could be dropped, so that State Pension eligibility is solely determined by 14 accumulation of years of full-time equivalent work. 38 The recent Independent Review of the State Pension argued for keeping a uniform SPA out of the principle of universality for the pension benefit, but to mitigate disadvantage through a means-tested one year early SPA for those who are unable to work through ill health or caring responsibilities.…”
Section: Discussionmentioning
confidence: 99%
“…8 This can be seen in the higher rate of disability pension uptake for lower social class groups. [9][10][11][12][13][14] With the tightening of eligibility rules for disability benefits, 15 a rising SPA could therefore have a disproportionate impact on people in lower social class groups, who are more likely to leave employment early due to health and unemployment reasons, 16;17 but are not eligible for incapacity benefit and must wait until increasingly older ages to qualify for a state pension. 18 However, no studies that have examined whether lower social class groups tend to have shorter or longer amounts of time between stopping work and death, compared to higher social class groups, or whether these social class differences exist for people in good and poor health.…”
Section: Introductionmentioning
confidence: 99%